The complex tapestry of free will: a philosophical odyssey - Kane, Robert (Oxford University Press, 2024)
"It is now more than half a century since I first began thinking about issues of free will. The libertarian views of free will I developed over this long period have been much debated and have been refined and further developed in response to the critical literature. The goal of this book is to provide an overview of recent developments of my views along with responses to the latest critical literature on them over the past twenty-five years since the publication of my book, The Significance of Free Will (OUP, 1996). Chapters 1-5 present an overview of my current view with the recent additions and alterations to it defended in greater detail. Chapters 6-10 include critical examinations of influential views of many philosophers in the past twenty-five years who have defended alternative views of free will and moral responsibility, including prominent defenders of competing libertarian views, prominent defenders of compatibilist views, free will skeptical views, revisionist views, illusionist views, and others. The goal of these chapters is not merely to criticize these views, but to show what I believe they get right and what aspects of many of them can be accommodated in the libertarian view of free will I defend here. In the final chapter 11, I relate the view of free will of earlier chapters to ethical views I have developed in other works over this same period and to the philosophy of religion, including Eastern religions (Hinduism, Buddhism) as well as theistic traditions (Judaism, Christianity, and Islam). Free will, moral responsibility, self-forming actions, ultimate responsibility, incompatilism, AC/EC libertarianism, plural voluntary control, teleological guidance control, will-setting"--